The Early Aptian (Cretaceous) stratigraphy of Mount Pagasarri (N Spain): Oceanic anoxic event‐1a. (20th October 2017) - Fernández‐Mendiola, Pedro A.; Mendicoa, Jone; Owen, Hugh G.; García‐Mondéjar, Joaquín
Abstract : Sedimentological, stratigraphical, palaeontological, and geochemical evidence from outcrops of the Early Aptian (Cretaceous) succession in Mount Pagasarri (northern Spain) dated by ammonites is described to elucidate the origin of organic carbon‐rich sediments and carbonate platforms in the Early Aptian of the northern margin of the Tethyan Ocean. A 1, 600‐m‐thick section spans the latest Barremian to the end of the Early Aptian and is divided into 3 units: a lower marine nearshore, a middle rudist‐coral shallow‐water carbonate platform, and a deeper‐water outer shelf. Deshayesites oglanlensis, D. forbesi, D. deshayesi and Dufrenoyia furcata ammonite zones are represented. Three organic carbon‐rich intervals are recognised. The oldest (top Barremian) is correlated with the Taxy Level of France/Germany. A second organic layer in the lower part of the Deshayesites deshayesi Zone sediments correlates with the Selli Event of Italy. A third organic‐carbon enriched layer in the D. furcata Zone sediments post‐dates the Aparein Level of the Aralar area in Spain. Carbon isotope curves reveal a brief negative excursion followed by a more prolonged positive trend during the Early Aptian interpreted as oceanic anoxic event 1a (OAE1a). Three carbonate platform growth phases are recognised in the Basque‐Cantabrian Basin with OAE1a being developed between carbonate platform Phases 1 and 2. The Peñascal Limestones (late Early Aptian) represent carbonate platform Phase 3 of the Basque‐Cantabrian Basin succeeded by ammonite‐bearing marls of the latest Early Aptian, reflecting platform demise and subsequent marine flooding. The Mount Pagasarri area is a key locality for study of the oceanic anoxic events in the Greenhouse Earth of the Early Aptian.